2023
DOI: 10.1002/jad.12140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of personal relative deprivation on the relationship between anger rumination and aggression during and after the COVID‐19 pandemic lockdown: A longitudinal moderated network approach

Abstract: Introduction: Several studies have demonstrated a directional link between rage rumination and aggression. However, recent research suggests that this relationship is bidirectional. The current study examined the complex relationships between anger rumination and aggression using a moderated network approach in a longitudinal design while considering personal relative deprivation. Method: A total of 665 participants (59.25% female, age mean±SD = 19.01 ± 1.25) were enrolled at two-time points. Assessments inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Our results showed that in the late stage of the pandemic, college students were likely to be plagued by anxiety. After COVID‐19 pandemic broke out, the Chinese government took various measures to stop the pandemic, such as quarantine or city lockdowns, which interrupted people's daily lives (Tang et al, 2020; Tao, Niu, Li, et al, 2023). Anxiety symptoms among college students may have been exacerbated by continuous restrictions and reduced communication (Xiao, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that in the late stage of the pandemic, college students were likely to be plagued by anxiety. After COVID‐19 pandemic broke out, the Chinese government took various measures to stop the pandemic, such as quarantine or city lockdowns, which interrupted people's daily lives (Tang et al, 2020; Tao, Niu, Li, et al, 2023). Anxiety symptoms among college students may have been exacerbated by continuous restrictions and reduced communication (Xiao, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In general, childhood traumas, including physical and emotional abuse and neglect and sexual abuse were associated with a higher risk of developing multiple psychiatric symptoms, including increased frequency and severity of psychotic, emotional, obsessive–compulsive symptoms, and interpersonal issues in adulthood ( 29 , 30 , 56 58 ). Personal relative deprivation has been indicated to mediate or aggravate the devastating effects of childhood maltreatment on many kinks of psychiatric disorders and behavioral problems ( 53 , 59 , 60 ). This effects may be more obvious in developing countries, where the socio-economic differentiation and income inequalities were more severe ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the traditional moderated mediation model approach (31), the network analysis approach can better enclose the dynamic association between symptoms (32). Furthermore, according to Tao et al (33), the moderated network is an excellent approach to efficiently explore moderating variables. Therefore, we use the Moderated Network Model (MNM) to investigate whether empathy (both affective and cognitive empathy) can moderate the bidirectional relationship between aggression and PSU.…”
Section: The Current Studymentioning
confidence: 99%
“…Furthermore, according to Tao et al. ( 33 ), the moderated network is an excellent approach to efficiently explore moderating variables. Therefore, we use the Moderated Network Model (MNM) to investigate whether empathy (both affective and cognitive empathy) can moderate the bidirectional relationship between aggression and PSU.…”
Section: Introductionmentioning
confidence: 99%